Improving pelvic movements during diving in football goalkeepers -effects of hip-lock training - Ito, Y. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to introduce Hip Rock to football goalkeepers and to investigate the differences in pelvic movement and lower limb joint torque exertion of the opposite leg before and after Hip Rock Training. All subjects in the training group improved the maximum value of hip extension torque in the opposite leg after training. The effect of the interaction was greater in the training group than in the control group in the demonstration of hip extension torque in the opposite leg. The stability of the pelvic musculature could be obtained, and the extension torque of the hip joint could be improved by gaining a sense of power to the ground. These results suggest that hip lock training and its application training can be useful for goalkeepers who are unable to lower their trunks in the direction of play or move their center of gravity smoothly